2020
DOI: 10.1088/1741-4326/abbc4a
|View full text |Cite
|
Sign up to set email alerts
|

Stellarator-tokamak energy confinement comparison based on ASDEX Upgrade and Wendelstein 7-X hydrogen plasmas

Abstract: A confinement database with mainly electron-heated hydrogen plasmas from ASDEX Upgrade and Wendelstein 7-X was assembled. Stellarator confinement scaling expressions describe both standard discharges in the stellarator and L-mode plasmas in the tokamak similarly well and indicate a similar quality of energy confinement in both devices. While the energy confinement time in ASDEX Upgrade benefits from the smaller aspect ratio of the device, the transport coefficients in Wendelstein 7-X appear to be smaller possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…As the plasma volume decreases from V max to V min (with fixed absorbed power), the power deposition to the electrons increases in proportion to the volume ratio V max /V min . At the same time, the energy confinement worsens in the same ratio [3], and this experimental fact coincides with the predictions of the STMCP model. As a result, both processes compensate mutually and the electron temperature remains unchanged (in normalized coordinates, of course).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As the plasma volume decreases from V max to V min (with fixed absorbed power), the power deposition to the electrons increases in proportion to the volume ratio V max /V min . At the same time, the energy confinement worsens in the same ratio [3], and this experimental fact coincides with the predictions of the STMCP model. As a result, both processes compensate mutually and the electron temperature remains unchanged (in normalized coordinates, of course).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, using the ratio q(a) = 1/ι -(a) in the scaling law, one can see that the stellarator transport is much worse than the tokamak one. Analysis of the energy transport in a tokamak using a critical gradient transport model [2] showed that the right hand side of this ratio should be increased by some factor [3]. In [4] we determine this factor and use the following relation:…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, whether the aforementioned dissimilarities are the result of different optimisation procedures or are inherent to the physics of the two magnetic configurations remains to be established. On the other hand, the obtained results and the comparison with the L mode Tokamak support the opinion that turbulence transport is the dominant effect in determining the Stellarator energy confinement time, once the devices are reasonably optimised for neoclassical transport [32].…”
Section: Comparison With the Tokamak In L Mode Of Confinementsupporting
confidence: 68%
“…The small difference is that the power degradation α P of metallic devices is not in the range between −0.60 and −0.53 (−0.66 in NBI-LHW and −0.67 in ECRH-LHW). The true dependence of plasma confinement on plasma shape and configuration has been studied for many years [31][32][33]. The κ a dependency in most of single devices was not given in [23], except 1.112 in JET-C and 0.86 in NSTX.…”
Section: Comparison With Recent Scalings From the Itpa Global H-mode ...mentioning
confidence: 99%